2014
DOI: 10.1152/ajpgi.00331.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrergic neuromuscular transmission in the mouse internal anal sphincter is accomplished by multiple pathways and postjunctional effector cells

Abstract: The effector cells and second messengers participating in nitrergic neuromuscular transmission (NMT) were investigated in the mouse internal anal sphincter (IAS). Protein expression of guanylate cyclase (GCα, GCβ) and cyclic GMP-dependent protein kinase I (cGKI) were examined in cryostat sections with dual-labeling immunohistochemical techniques in PDGFRα(+) cells, interstitial cells of Cajal (ICC), and smooth muscle cells (SMC). Gene expression levels were determined with quantitative PCR of dispersed cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 50 publications
4
49
0
Order By: Relevance
“…This region is of interest because the frequency and amplitude of slow waves has been reported to be greatest in the most distal region of the IAS 12. In the mouse IAS, ICC‐MY have been reported to be few in number, not form a network and to decline distally 12, 13, 14. In keeping with these previous studies, only a very small number of ICC‐MYs were observed in the ASR.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This region is of interest because the frequency and amplitude of slow waves has been reported to be greatest in the most distal region of the IAS 12. In the mouse IAS, ICC‐MY have been reported to be few in number, not form a network and to decline distally 12, 13, 14. In keeping with these previous studies, only a very small number of ICC‐MYs were observed in the ASR.…”
Section: Discussionsupporting
confidence: 67%
“…The results obtained here for the mouse terminal bowel are therefore in line with previous reports on other parts of the GI tract in two other species, indicating that a reduction in ICC network volume during ageing may be a general phenomenon. Evidence that ICC play a critical role in regulation of smooth muscle contractility is now widely accepted15 including in the terminal bowel 13. These results therefore suggest that changes in ICCs during ageing described here may be an important factor in the physiological changes observed in this region.…”
Section: Discussionsupporting
confidence: 63%
“…However, the detailed regulation of nitrergic neurotransmission is still incompletely understood. Previous studies already showed an intricate modulation of spontaneous contractions via NO‐GC in smooth muscle cells (SMC), interstitial cells of Cajal (ICC) as well as fibroblast‐like cells (FLC) . The nitrergic impact on long distance contractions (LDCs), the main propulsive motor pattern in mice, was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the young murine IAS contracts following stimulation of excitatory cholinergic neurons, the release of acetylcholine (ACh) and activation of both M2 and M3 receptors which increase intracellular Ca 2+ and reduce cAMP, respectively, prolonging the activity of myosin light chain kinase . For appropriate defecation, the young IAS is relaxed by a combination of inhibitory neurotransmitters, including nitric oxide, ATP (or another purine) and vasoactive intestinal peptide (VIP) . There is some evidence for the co‐localization of the inhibitory neurotransmitters in specific motor neurons in both mouse and human gastrointestinal tissue .…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence for the co‐localization of the inhibitory neurotransmitters in specific motor neurons in both mouse and human gastrointestinal tissue . The release of these inhibitory transmitters is frequency dependent with purinergic transmitters released at the lowest firing frequency, followed by NO and then VIP as the neuronal firing frequencies increase . In the mouse, release of these neurotransmitters typically hyperpolarizes IAS circular smooth muscle cells, closing voltage gated calcium channels and reducing intracellular calcium .…”
Section: Introductionmentioning
confidence: 99%